2019
DOI: 10.1101/725580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary dynamics of microbial communities in bioelectrochemical systems

Abstract: SUMMARYBio-electrochemical systems can generate electricity by virtue of mature microbial consortia that gradually and spontaneously optimize performance. To evaluate selective enrichment of these electrogenic microbial communities, five, 3-electrode reactors were inoculated with microbes derived from rice wash wastewater and incubated under a range of applied potentials. Reactors were sampled over a 12-week period and DNA extracted from anodal, cathodal, and planktonic bacterial communities was interrogated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…The electrochemical results from inocula screening indicated that the most electroactive consortia were obtained from the lakes that indicated the highest Cu content, ORP, and conductivity (yellow and purple, Table 1), which is consistent with previous studies pertaining to the effect of set potential on electrogenic biofilm growth [33,[47][48][49][50][51]. Colorful lakelets contained various Cu and Zn oxyminerals, and hence expected to be a relevant source of electroactive bacteria [42,[52][53][54].…”
Section: Sequencing and Biofilm Investigationsupporting
confidence: 86%
“…The electrochemical results from inocula screening indicated that the most electroactive consortia were obtained from the lakes that indicated the highest Cu content, ORP, and conductivity (yellow and purple, Table 1), which is consistent with previous studies pertaining to the effect of set potential on electrogenic biofilm growth [33,[47][48][49][50][51]. Colorful lakelets contained various Cu and Zn oxyminerals, and hence expected to be a relevant source of electroactive bacteria [42,[52][53][54].…”
Section: Sequencing and Biofilm Investigationsupporting
confidence: 86%
“…Functional analyses of metagenomes from our lab scale experiments was sufficient to reveal metabolic changes between different species of the MFC dominant genus, Geobacter, suggesting that optimal nutrient utilization at the lowest electrode potential is achieved via genome rearrangements and a strong inter-strain selection, as well as adjustment of the characteristic syntrophic relationships. These observations show a certain degree of metabolic and genomic plasticity of electrochemically active bacteria and their communities in adaptation to adverse anodic and cathodic compartments (Szydlowski et al, 2019).…”
Section: Introductionmentioning
confidence: 74%
“…NADH-quinone oxidoreductase (nuoB/C/G/L, nuoD. nuoH genes) and NADH-ubiquinone oxidoreductase (nad3) genes show the strongest dependence on the applied potential and their abundancy evolves strongly over the period of the experiment (Szydlowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The high abundance of EET-related and hydrocarbon degrading genes in pH 7 OCP, as seen in Table 1, as well as the total number of unique annotations may reflect higher metabolic diversity of this community due to the lack of external electron circuit. Indeed previous studies comparing MFC communities (Ishii et al, 2018;Kouzuma et al, 2018;Szydlowski et al, 2020) reveal higher functional diversity in communities grown at OCP, whereas the presence of external circuit applies selective pressure on the microbial metabolism.…”
Section: Discussionmentioning
confidence: 95%